Compressive properties of biomedical open-cell Zn foam. (18th October 2019) - Wang, Dingding; Zhang, Xuan; Zu, Guyin; Qiao, Aike; He, Yongdong; Mu, Yongliang
Abstract: In the present work open-cell Zn foam, as potential biodegradable materials for medical use, was fabricated by vacuum infiltration casting technology. The structure, compressive properties, energy absorption and hardening behavior of open-cell Zn foams with various porosity and cell size were investigated. A finite element analysis (FEA) was employed to simulate the deformation behavior of open-cell Zn foams during compression. Results showed that Zn foams with larger cell size and lower porosity exhibited higher compressive strength and energy absorption capacity. Instead of sudden collapse, the global continuous deformation of open-cell Zn foam during compression was observed even though brittle fracture is the primary failure mode of Zn matrix. The open-cell Zn foam in this study also showed higher cell structure sensitivity than that forecasted by Gibson-Ashby model. Moreover, it can be found that there is a significant smooth hardening region rather than a fluctuant plateau region on compressive stress-strain curves. These can be attributed to the coexistence of two types of cell structures, which are called 'cell wall' structure and 'struts' structure in the open-cell Zn foams. The successive occurrences of multiple deformation bands, cooperative deformation of both cell structures and early densification of cell during compression can account for the smooth flow hardening behavior of open-cell Zn foam. In addition, FEA estimation for unit-cell models, both cell wall model as well as struts model, also indicated a continuous emergence and bending of plastic hinge.